2007
DOI: 10.1111/j.1462-2920.2006.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Putative ammonia‐oxidizing Crenarchaeota in suboxic waters of the Black Sea: a basin‐wide ecological study using 16S ribosomal and functional genes and membrane lipids

Abstract: Within the upper 400 m at western, central, and eastern stations in the world's largest stratified basin, the Black Sea, we studied the qualitative and quantitative distribution of putative nitrifying Archaea based on their genetic markers (16S rDNA, amoA encoding for the alfa-subunit of archaeal ammonia monooxygenase), and crenarchaeol, the specific glycerol diphytanyl glycerol tetraether (GDGT) of pelagic Crenarchaeota within the Group I.1a.Marine Crenarchaeota were the most abundant Archaea (up to 98% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
201
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(215 citation statements)
references
References 61 publications
(128 reference statements)
13
201
1
Order By: Relevance
“…Gene copies at 450 m were comparable to those in the upper portion of the water column, and reached 10 4 copies per milliliter in the Carmen Basin. Relatively high archaeal amoA abundances under suboxic conditions are in line with a number of previous studies: expansions of marine archaea may occur during oceanic anoxic events (Kuypers et al, 2001), archaeal amoA genes have been recovered from the OMZ of the ETNP and from the suboxic zone of the Black Sea (Francis et al, 2005), and archaeal amoA copy numbers were maximal in the suboxic zone of the Black Sea (Coolen et al, 2007;Lam et al, 2007). In an interesting parallel, the distribution of marine Crenarchaeota based on their membrane lipid, crenarchaeol, showed consistently high abundances at 450 m in the OMZ of the Arabian Sea (Sinninghe Damste et al, 2002).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Gene copies at 450 m were comparable to those in the upper portion of the water column, and reached 10 4 copies per milliliter in the Carmen Basin. Relatively high archaeal amoA abundances under suboxic conditions are in line with a number of previous studies: expansions of marine archaea may occur during oceanic anoxic events (Kuypers et al, 2001), archaeal amoA genes have been recovered from the OMZ of the ETNP and from the suboxic zone of the Black Sea (Francis et al, 2005), and archaeal amoA copy numbers were maximal in the suboxic zone of the Black Sea (Coolen et al, 2007;Lam et al, 2007). In an interesting parallel, the distribution of marine Crenarchaeota based on their membrane lipid, crenarchaeol, showed consistently high abundances at 450 m in the OMZ of the Arabian Sea (Sinninghe Damste et al, 2002).…”
Section: Resultssupporting
confidence: 68%
“…arb-home.de) (Ludwig et al, 2004). GOC sequences from 60 and 450 m were compared with all previously reported sequences at least 540 bp in length from marine water columns (Francis et al, 2005;Hallam et al, 2006b;Wuchter et al, 2006;Coolen et al, 2007;Lam et al, 2007;Mincer et al, 2007), coastal and estuarine sediments (Francis et al, 2005;Beman and Francis, 2006), soils (Francis et al, 2005;Leininger et al, 2006), wastewater treatment plants (Park et al, 2006) and corals -as well as reference sequences from soil fosmid 54d9 (Schleper et al, 2005), Cenarchaeum symbiosum (Hallam et al, 2006b) and N. maritimus (Kö nneke et al, 2005). Distanceand parsimony-based bootstrap analyses were conducted in PAUP *4.0b10 (Sinauer Associates, Sunderland, MA, USA) and used to estimate the reliability of phylogenetic reconstructions with 200 replicates.…”
Section: Pcr and Analysis Of Community Compositionmentioning
confidence: 99%
“…GDGTs are preserved well in the sedimentary record and can thus be used as biomarkers for this group of Archaea (e.g. Kuypers et al, 2001;Pancost et al, 2001;Ingalls et al, 2006;Coolen et al, 2007). Schouten et al (2002) found a correlation between sea surface temperature (SST) and the distribution of four specific GDGTs present in sediment core tops (GDGT-1, -2, -3 and -4 0 , Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Mesophilic archaea are ubiquitous and abundant members of diverse marine environments including coastal waters (Mincer et al, 2007;Beman et al, 2010), marine sediments, estuaries (Mosier and Francis, 2008;Bernhard et al, 2010;Urakawa et al, 2010), stratified basins (Coolen et al, 2007;Lam et al, 2007) and open ocean water columns (Beman et al, 2008;Church et al, 2010;Santoro et al, 2010). The recent cultivation of the first mesophilic marine archaeon, Nitrosopumilus maritimus, (Konneke et al, 2005;Martens-Habbena et al, 2009), two thermophilic archaea, Nitrosocaldus yellowstonii and Nitrosophaera gargensis (Hatzenpichler et al, 2008;de la Torre et al, 2008) and a freshwater archaeon, Nitrosoarchaeum limnia (Blainey et al, 2011) established that at least some of these organisms are chemolithoautotrophic ammonia oxidizers.…”
Section: Introductionmentioning
confidence: 99%